Interactive History Learning: Development of Canva-Based Materials at State Senior High School 7 Pontianak - Sukowati, Mekar Enggal; Rizky, Shofia; Suparno, Suparno; Junivan, Banuarea Hosea (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to improve student academic achievement through the development of Canva-based teaching materials in class X-A of SMA Negeri 7 Pontianak in the 2024/2025 academic year. Through a classroom action research approach that combines observation, interviews, questionnaires, and tests, a significant picture of development was obtained in each learning cycle. The evaluation results showed an increase in scores from Cycle II by 48.57%, increasing in Cycle III to 66.28%, and finally reaching 84.41% in Cycle IV, thus exceeding the minimum completion limit of 75. In addition to improving student achievement, this activity also encouraged teachers to improve their ability to design and utilize digital learning resources that are more creative and relevant to student needs. Student responses also showed a positive tendency, especially regarding ease of access and the visual appearance of the teaching materials, which were considered more interesting and helped understand the material. Overall, these findings confirm that the use of Canva-based interactive teaching media can make a real contribution to improving the quality of the learning process and student learning outcomes.